Pendekatan Komunikasi Multikultural Dalam Membangun Hidup Yang Harmonis Masyarakat Merauke - Batmyanik, Aloysius (Jurnal Masalah Pastoral, 2017)
Recently, too many conflict events that run down Indonesia. To solve the problems, Indonesia government was used the structural and cultural approach by the several indicators as the culture, politic, journalistic multicultural communication, moral educating, but it was not successful. Today the government rethinks the other policy approach to face many conflicts and demonstrations, as the logic consequency of the new system of the regency autonomy, is the educational multicultural approach. To improve the objective of the government policy, I do the study.The study aims to analyze the library research of the communication multicultural approach in the building of the harmonization society life in Merauke Regency.The process of this study is the analyzing that how the society in Merauke Rengency since 2000 until 2017 was still peacefull and hamony? The result of this study found that: there is a main value that becomes the foundation in interaction and dymic of the society life is “Izakot Bekai, Izakot Kai” (one heart, one goal). To build the society peacefull and harmony life, the leader of Merauke regency was used the multicultural communication approach. Impact of the implementation on the main value that mentioned above is: (a) becoming the ideology of the every member of the Merauke society that must be implemented in every words and action to build the unity and unification; (b) to pressing down the discrimination atittude, group, etnic, cultur and religion, so that each member of the society can accept, respect, each other; (c) becoming the weapon to prefentive the radical groups, separatis groups, that want to provocative Merauke people to disintegrate the unity and unification; (d) becoming the important instrument and foundation of the multicultural communication, that be guarantee of the peacefull and harmony of the Merauke society life; (e) to synchronize the different values and the same values into the one main value is “one heart, one goal”that become always the spirit life of the Merauke regency, dan (f) becoming the umbrella for the Mereauke regency to protect from the conflicts and demonstrations.